Examining the Impact of Social Assistance on Poverty: A Bibliometric Analysis - Dian Lestari; Sumardi Sumardi (Journal of Government and Politics (JGOP), 2024)
Does social assistance provide benefits at the level necessary to escape poverty? Our literature search found many studies that sought answers to this question. Therefore, this research aims to investigate the dominant theme in publications related to the impact of social assistance on poverty. This research uses bibliometric analysis using RStudio software with the Scopus database. The data collected was processed using RStudio software to produce visualizations and analyze research trends and topic developments regarding the impact of social assistance on poverty. The most cited articles in 2021 had an annual average citation of 1.9, which shows that the articles in that year were extraordinary. The International Journal of Social Welfare has produced 11 articles and is the most productive source. Since the beginning of 2013, the International Journal of Social Welfare has published more than any other source. In this theme, the United States has the most citations; next, Canada and China are the second and third most cited countries. The United States received the highest 378 citations, while Canada and China received 303 and 280 citations. Barrientos is the most contributing author with the highest H-index score of 6, followed by Walker and Gao with an H-index of 5 and 4, respectively. However, what is most interesting in this finding is that Word cloud Poverty (12%) is the most prominent keyword length. Social assistance was only announced at 2%. Research on the impact of social assistance on poverty is still an exciting topic for future research.